2017
DOI: 10.1017/s1092852917000141
|View full text |Cite
|
Sign up to set email alerts
|

Social and psychological consequences of not crying: possible associations with psychopathology and therapeutic relevance

Abstract: Despite reduced empathy, less connection with others, and a more avoidant/less anxious attachment type, well-being is maintained in tearless people. Additional clinical and therapeutic investigations of tearlessness may lead to clarification of bidirectional associations between psychiatric disorders (e.g., alexithymia, posttraumatic stress disorder, psychopathy) and tearlessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Some research focused on the crier’s experience has begun to emerge, with research comparing people who had lost the ability to cry and those who could. For example, Hesdorffer et al (2017) found no differences between the two groups on their ratings of well-being but did find that people who could cry felt more socially connected with others than those who could not. These findings suggest that crying may assist in creating feelings of social connectedness, yet it is still unclear whether that social connection and help happens during the crying experience itself or, perhaps, because crying encourages a person to seek help afterward.…”
Section: Crying and The Social Contextmentioning
confidence: 86%
“…Some research focused on the crier’s experience has begun to emerge, with research comparing people who had lost the ability to cry and those who could. For example, Hesdorffer et al (2017) found no differences between the two groups on their ratings of well-being but did find that people who could cry felt more socially connected with others than those who could not. These findings suggest that crying may assist in creating feelings of social connectedness, yet it is still unclear whether that social connection and help happens during the crying experience itself or, perhaps, because crying encourages a person to seek help afterward.…”
Section: Crying and The Social Contextmentioning
confidence: 86%
“…Consistent with this idea, Benecke (2009) found that patients with a range of psychiatric disorders who cried during a clinical interview reported feeling closer or related more to others and were also less aggressive in both their self-reported emotions and facial expressions relative to noncrying patients. Similarly, Hesdorffer et al (2018) observed that noncriers (relative to criers) had lower empathy scores and reported feeling less connected with others and receiving of less social support.…”
Section: Tears In the Clinical Settingmentioning
confidence: 87%
“…Exposure therapy in the context of trauma work, such as prolonged exposure (Foa et al, 2007; Peterson, Foa, & Riggs, 2011), may also facilitate the processing of emotions, including crying, where crying may be a sign of therapeutic progress. Tearless patients may also experience a more general emotional numbness that hinders their ability to connect with others, and tearlessness may hinder the solicitation of emotional support, which may be a critical mechanism involved in the facilitation of the beneficial effects of crying (see Gračanin et al, 2014; Hesdorffer et al, 2018). Psychotherapy to facilitate emotional processing and expression may also help tearless individuals to use interpersonal support better.…”
Section: Tears In the Clinical Settingmentioning
confidence: 99%
“…A more positive attitude toward crying and increased awareness of its impact on others may facilitate crying as a more functional coping mechanism, eliciting more support from others and reducing interpersonal difficulties (cf. [25]).…”
Section: Discussionmentioning
confidence: 99%